2023
DOI: 10.1038/s41598-023-35917-8
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of hepatic transcriptional profiles reveals genetic regulation of atherosclerosis in hyperlipidemic Diversity Outbred-F1 mice

Abstract: Atherogenesis is an insipidus but precipitating process leading to serious consequences of many cardiovascular diseases (CVD). Numerous genetic loci contributing to atherosclerosis have been identified in human genome-wide association studies, but these studies have limitations in the ability to control environmental factors and to decipher cause/effect relationships. To assess the power of hyperlipidemic Diversity Outbred (DO) mice in facilitating quantitative trait loci (QTL) analysis of complex traits, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Interestingly, a recent mouse genetic study identified a QTL for atherosclerotic lesions at the Asah2 locus in male mice ( 88 ). This study utilized a DO-F1 mouse population, generated by breeding DO mice to cholesteryl ester transfer protein;ApoE3-Leiden mice to produce an F1 generation with increased susceptibility to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent mouse genetic study identified a QTL for atherosclerotic lesions at the Asah2 locus in male mice ( 88 ). This study utilized a DO-F1 mouse population, generated by breeding DO mice to cholesteryl ester transfer protein;ApoE3-Leiden mice to produce an F1 generation with increased susceptibility to atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%